2012
DOI: 10.3345/kjp.2012.55.8.280
|View full text |Cite
|
Sign up to set email alerts
|

Birth statistics of high birth weight infants (macrosomia) in Korea

Abstract: PurposeThe authors analyzed the trend from the birth-related statistics of high birth weight infants (HBWIs) over 50 years in Korea from 1960 to 2010.MethodsWe used 2 data sources, namely, the hospital units (1960's to 1990's) and Statistics Korea (1993 to 2010). The analyses include the incidence of HBWIs, birth weight distribution, sex ratio, and the relationship of HBWI to maternal age.ResultsThe hospital unit data indicated the incidence of HBWI as 3 to 7% in the 1960's and 1970's and 4 to 7% in the 1980's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…The risk of LBWIs and very LBWIs was high in mothers ≥ 35 years and the proportion of advanced maternal age and LBWIs in older mothers has increased 1829. In a study analyzing birth statistics from 1960 to 2010, both hospital unit and Statistics Korea data showed that the higher the maternal age, the higher the risk of both high birth weight infant (HBWI) and LBWI 30. In a survey using hospital data, maternal age ≥ 35 years was associated with LBWIs, Apgar scores less than 7, and chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of LBWIs and very LBWIs was high in mothers ≥ 35 years and the proportion of advanced maternal age and LBWIs in older mothers has increased 1829. In a study analyzing birth statistics from 1960 to 2010, both hospital unit and Statistics Korea data showed that the higher the maternal age, the higher the risk of both high birth weight infant (HBWI) and LBWI 30. In a survey using hospital data, maternal age ≥ 35 years was associated with LBWIs, Apgar scores less than 7, and chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Data from Statistics Korea reported that the percentages of HBW infants among total live births decreased over the years as follows: 6.7% (1993), 6.3% (1995), 5.1% (1997), 4.5% (2000), and 3.5% (2010). Between 1993 and 2010, the average BW of Korea was reduced from 3.31 kg in 1993 to 3.22 kg in 2010 by approximately 0.1 kg ( 30 ). Recent changes in percentages of HBW infants and average BW could help to explain why the new curves are shifted down in the older GA on the appropriate GA and large for GA curves.…”
Section: Discussionmentioning
confidence: 99%
“…Актуальность проблемы макросомии плода обусловлена в первую очередь высокой частотой перинатальной заболеваемости и смертности в сравнении со среднестатистическими показателями [3,[38][39][40].…”
Section: перинатальные исходы родов крупным плодомunclassified